Cell‐Substrate Interactions: Tuning of Collagen Scaffold Properties Modulates Embedded Endothelial Cell Regulatory Phenotype in Repair of Vascular Injuries In Vivo (Adv. Healthcare Mater. 15/2015). Issue 15 (27th October 2015) - Unterman, Shimon; Freiman, Alina; Beckerman, Margarita; Abraham, Eytan; Stanley, James R. L.; Levy, Ela; Artzi, Natalie; Edelman, Elazer
Abstract : Biomaterials exhibit dramatically varying behavior and efficacy in different tissue microenvironments. On p. 2220, S. Unterman, N. Artzi, and co‐workers describe how tuning material properties can enhance efficacy of implanted endothelial cells in the injured perivascular environment. The rational design of materials for optimal in vivo efficacy is dependent on real‐time monitoring of tissue, material (red), and implanted cell (green) state using live animal fluorescent imaging.